A Comparative Clinical Study on the Efficacy of Kala Basti and Kati Basti Along with Nirgundighan Vati in the Management of Gridhrasi (Sciatica) - Sharma, Akanksha; Makodiya, Anjali; Ramani, Hetal; Ruparel, Sweety (International Research Journal of Ayurveda & Yoga, 2022)
The most common disorder which affects the movement of legs, particularly in the most productive period of life i.e 30 to 50 years is the problem of back ache which turns into Sciatica. The signs and symptoms of Sciatica can be correlated to Ghridhrasi. Analgesics or surgery are the only remedies for this disease, which may sometimes produce systemic side effects. Acharya Charak has described Basti as the line of treatment in Ghridhrasi. So Kala Basti is selected. As Nirgundi acts as Rujapha and Vatashleshma prashmani. So Nirgundi Ghan Vati is selected for Shaman drug. Kati Basti is selected to break local Samprapti, as it is a type of Bahirparimarjin Chikitsa. Aim: To compare the effect of Kala Basti and Kati Basti along with Nirgundi ghana Vati in the management of Gridhrasi. Material and methods: For present study, 30 Patients of Gridhrasi were randomly divided into 2 groups from the OPD & IPD of Govt. Akhandanand Ayurved Hospital, Ahmedabad. Result: 13.33% of patients had Complete remission, Marked improvement was found in 13.33% and 40% of the patients had Moderate improvement. 33.33% of the patient showed Mild improvement. Conclusion: Kala Basti with Nirgundi taila as Anuvasana and Erandmool Kwath in Niruha Basti followed by Shamana therapy with Nirgundi ghan Vati provided better results in Ghridrasi especially Vatakaphaj Ghridrasi.